TINGKAT PENGETAHUAN, SIKAP DAN PERILAKU MASYARAKAT PESISIR LINGKUNGAN PATTITANGNGANG KELURAHAN TAKALAR TENTANG PENTINGNYA SANITASI LINGKUNGAN - HASRIANTI, HASRIANTI; NURHASANAH, NURHASANAH; RAHMITA, RAHMITA (GANEC SWARA, 2024)
Environmental sanitation is an activity that aims to maintain and maximize basic environmental condition standards that will affect human life. Poor environmental sanitation will cause environmental problems. This research was conducted to determine the level of knowledge, attitudes and behavior of coastal communities in the Pattitannggang Environment, Takalar District regarding the importance of environmental sanitation. This research was conducted in the coastal area of the Pattitanggang Environment, Takalar Village, Mappakasunggu District, Takalar Regency. Data collection was carried out using survey, documentation and interview methods with a questionnaire guide. Interviews with 25 coastal community respondents. The results of the research show that coastal communities in the Pattitangang Environment have a fairly good level of knowledge, attitudes and behavior regarding the importance of environmental sanitation. However, environmental cleaning facilities and infrastructure such as rubbish bins or rubbish trucks are not yet available, so people continue to carry out the habit of piling up and burning rubbish which can have an impact on reducing air quality